SYARAT BATAS SERAP PADA GELOMBANG AKUSTIK DUA DIMENSI - Mohammad Mahfuzh Shiddiq (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2011)
Acoustic wave equation with Dirichlet and Neumann boundary conditions causeincident wave was perfectly reflected at edge. Thus, it is used absorbing boundary conditionsthat produce no reflection. In this paper, we would like find approximation of absorbingconditions that produce reflection coefficient as small as possible and smaller than thoseobtained from Dirichlet and Neumann boundary conditions.